Pelatihan Budidaya Cacing Sutera (Tubifex sp.) Ramah Lingkungan di Talang Rimbo Lama, Kabupaten Rejang Lebong - Hamka, Muhammad Subhan; Rahmadiah, Triayu; Nafsiyah, Ikromatun; Ketaren, Cyrum Barnike Beru; Sriyanti, Asih; Sumarni, NetI; Hadi, Sadisman (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2022)
Silkworm culture media (Tubifex sp.) are very important because it can be affected on growth and nutrient content of silkworm, such as fruit and vegetable waste. The waste disposal of fruit and vegetable in Rejang Lebong Regency have not been used properly, therefore this counseling aims of management of the waste of fruit and vegetable as and environmentally friendly silkworm culture media in Talang Rimbo Lama, Rejang Lebong Regency. The approach used includes meeting with the partnership, counseling, demonstrating, and evaluating. The counseling was interactive and communicative, and participants showed that considerable interest on materials presented. This counseling can improve knowledges and skills about silkworm cultivation and the use of the waste of fruit and vegetable as a silkworm culture media.